Child hand contamination is associated with subsequent pediatric diarrhea in rural Democratic Republic of the Congo (REDUCE Program). Issue 1 (14th December 2020) - George, Christine Marie; Cirhuza, Lucien Bisimwa; Birindwa, Alves; Williams, Camille; Beck, Sara; Julian, Timothy; Kuhl, Jennifer; Coglianese, Nicole; Thomas, Elizabeth; Bauler, Sarah; François, Ruthly; Saxton, Ronald; et al.
Abstract: Objective: The Reducing Enteropathy, Undernutrition, and Contamination in the Environment (REDUCE) program focuses on identifying exposure pathways to faecal pathogens for young children in the Democratic Republic of the Congo (DRC) and on developing scalable interventions to reduce faecal contamination from these pathways. Methods: A prospective cohort study of 690 participants was conducted to investigate the association between hand, food, and environmental faecal contamination and diarrhoeal disease prevalence among young children in Walungu Territory, South Kivu, DRC. A total of 1923 hand rinse, soil, food, object, surface, stored water and water source samples were collected during unannounced spot checks after baseline enrolment and analysed for Escherichia coli . Caregiver reports of diarrhoea were obtained from children < 5 years at a 6‐month follow‐up. Results: E.coli was detected in 73% of child and caregiver hand‐rinse samples, 69% of soil samples from child play spaces, 54% of child food samples, 38% of objects and surfaces children were observed putting in their mouths, 74% of stored water samples, and 40% of source water samples. Children < 5 years with E. coli on their hands had significantly higher odds of diarrhoea at the 6‐month follow‐up (odds ratio: 2.03 (95% confidence interval: 1.05, 3.92)). Conclusion: The cohort study findings from the REDUCE program have shown that child hand contamination is associated with diarrhoeal disease in rural DRC, and that there is high faecal contamination in child plays spaces and food. These findings provide evidence demonstrating the urgent need to provide clean play spaces for young children and interventions targeting hand hygiene to reduce paediatric exposure to faecal pathogens. Abstract : Objectif: L'étude REDUCE (Réduire l'Entéropathie, la Dénutrition et la Contamination à partir de l'Environnement) se concentre sur l'identification des voies d'exposition aux pathogènes fécaux pour les jeunes enfants en République Démocratique du Congo (RDC) et sur le développement d'interventions évolutives pour réduire la contamination fécale par ces voies. Méthodes: Une étude de cohorte prospective de 690 participants a été menée pour étudier l'association entre la contamination fécale des mains, des aliments et de l'environnement et la prévalence des maladies diarrhéiques chez les jeunes enfants dans le Territoire de Walungu, dans le Sud‐Kivu, en RDC. Un total de 1.923 échantillons de rinçages des mains, de sol, d'aliments, d'objets, de surfaces, d'eau stockée et de sources d'eau ont été collectés lors de contrôles ponctuels inopinés après l'inscription de base et analysés pour Escherichia coli . Les rapports des soignants concernant la diarrhée ont été obtenus pour les enfants de moins de 5 ans à un suivi de 6 mois. Résultats: E. coli a été détecté dans 73% des échantillons de rinçage des mains des enfants et des soignants, 69% des échantillons de sol des aires de jeux pour enfants, 54% des échantillons d'aliments pour enfants, 38% des objets et des surfaces que les enfants mettaient en bouche, 74 % des échantillons d'eau stockée et 40% des échantillons de sources d'eau. Les enfants de moins de 5 ans avec E. coli sur leurs mains avaient un risque de diarrhée significativement plus élevé au suivi de 6 mois (rapport de cotes: 2, 03 (intervalle de confiance à 95%: 1, 05, 3, 92)). Conclusion: Les résultats de l'étude de cohorte du programme REDUCE ont montré que la contamination des mains des enfants est associée aux maladies diarrhéiques dans les régions rurales de la RDC et à une forte contamination fécale dans les aires de jeux et les aliments pour enfants. Ces résultats fournissent des données démontrant le besoin urgent de fournir des espaces de jeu propres aux jeunes enfants et des interventions ciblant l'hygiène des mains pour réduire l'exposition pédiatrique aux pathogènes fécaux.